EFFECTIVENESS OF DIRECT CASH ASSISTANCE IN INDEPENDENT VILLAGES IN BARRU REGENCY - Idrus, Jemmy (Transpublika Publisher, 2022)
This study aims to identify problems that occur in the distribution process, suitability of the Beneficiary Determination Criteria (KPM), the amount and use of direct cash assistance by KPM in independent villages, and provide recommendations for strategies used to increase the effectiveness of direct cash assistance distribution for residents of independent villages. This research was conducted in villages that have status as Independent Villages in Barru Regency, namely Kading Village, Lompo Tengah Village, Cilelang Village, Bojo Village, Gattareng Village, Pujananting Village and Pancana Village. The research method uses a sequential mixed method, namely a quantitative method which is then followed by a qualitative method. The results of the analysis show that the implementation of Direct Cash Assistance through Village Funds (BLT DD) Independent Village, Barru Regency, South Sulawei Province can be carried out well as the process of implementing the distribution of BLT DD has been running optimally based on its legal basis. Obstacles to the implementation of BLT DD distribution activities were influenced by internal and external factors. The internal factor in the distribution of BLT DD is the regulation regarding the mechanism for distributing BLT DD which can be called not according to schedule. The effectiveness of the Distribution of Direct Cash Assistance to Village Funds in an Effort to Help Poor Communities Affected by Covid-19 in Independent Villages, Barru Regency is said to have been effective.